Potential Application of Land Art in Marketing - Denis VASILIEV (Communications of International Proceedings, 2020)
Modern companies intend to implement and communicate sustainable business practices. Moreover, marketing communications aim to attract attention of target audiences through differentiation. At the same time, philosophy of Land Art movement and high visibility of its artworks have a great potential to be appealing to environmentally conscious customers and to allow the company to “stand out from the crowd”. Surprisingly, application of Land Art in marketing is not discussed in scientific literature and the opportunity to use this synergy is largely overlooked by companies. Thus, using conceptual research approach – theory adaptation, I demonstrate how Land Art can be used by modern companies to enhance their branding, place marketing and PR activities, as well as achieve high level of customer engagement. I also discuss potential use of Land art as a part of integrated marketing communications, with particular emphasis on enhancement of digital communications effectiveness. Exploration of all these areas of Marketing leads to a conclusion that there is an urgent need for research and practical application of Land Art in marketing.
Keywords: Earth art; environmental art; advertising; branding; PR